Conceptual framework for personal recovery in mental health: systematic review and narrative synthesis - Leamy, Mary; Bird, Victoria; Boutillier, Clair Le; Williams, Julie; Slade, Mike (British journal of psychiatry, 2011)
No systematic review and narrative synthesis on personal recovery in mental illness has been undertaken. To synthesise published descriptions and models of personal recovery into an empirically based conceptual framework. Systematic review and modified narrative synthesis. Out of 5208 papers that were identified and 366 that were reviewed, a total of 97 papers were included in this review. The emergent conceptual framework consists of: (a) 13 characteristics of the recovery journey; (b) five recovery processes comprising: connectedness; hope and optimism about the future; identity; meaning in life; and empowerment (giving the acronym CHIME); and (c) recovery stage descriptions which mapped onto the transtheoretical model of change. Studies that focused on recovery for individuals of Black and minority ethnic (BME) origin showed a greater emphasis on spirituality and stigma and also identified two additional themes: culturally specific facilitating factors and collectivist notions of recovery. The conceptual framework is a theoretically defensible and robust synthesis of people's experiences of recovery in mental illness. This provides an empirical basis for future recovery-oriented research and practice.